Narratives of youth climate activism: Exploring the diversity of meaning-making on climate change and citizenship - Fonseca, A.; Castro, P. (Journal of Environmental Psychology, 2026)
The psychology of climate change (CC) has been more attentive to people as “green” consumers than as citizens. Moreover, when looking at people's roles as citizens, it focuses more on individual motivations to join collective action, and less on the plural views of stable members of CC activist-collectives – who, however, occupy their place in citizenship by relating in contrasting ways with State institutions and policies and by making competing rights-claims. Drawing from an interdisciplinary framework connecting the approach of social representations with political science's models of citizenship, this paper explores interviews (N = 28) with young Portuguese activists stably engaged in three different types of CC activist-collectives. It aims to understand the shared narratives of CC and citizenship that the interviewees construct. For this, it identifies the narrative-elements (temporalities, actors, narrative-roles) in their accounts, and explores how they make-sense of citizenship, i.e. how they view State institutions and policies, what claims of rights-and-duties they make, and to what extent they reflect on their own and Others' positions. Three narratives were identified: a conciliating narrative defending consensus-building for institutional reform, a confrontational narrative calling for systemic rupture through resistance to (current) institutions, and an experimental one proposing community-based innovation. Displaying also different forms of reflecting on Self and Other, these narratives showcase the plurality of meanings around CC, citizenship, social change and future imaginaries of stable young activists. They highlight the value of qualitative and interdisciplinary approaches for a processual, relational environmental psychology, capable of grasping the diversity and consequentiality of people's climate engagements as citizens.